Successful Remote Work: What Employees’ Skills are Essential for It? - Lazauskaitė-Zabielskė, Jurgita; Žiedelis, Arūnas; Urbanavičiūtė, Ieva (Psichologija, 2022)
As remote work becomes a custom way of work organization, there is a need to research the factors that determine its effectiveness. Based on remote work research conducted in Europe and Lithuania, the article presents the differences between remote work and office work, based on which several employee skills are distinguished for effective remote work. First, due to longer working hours and the constant availability of electronic communication and information tools, the psychological skills of detaching from work are discussed. Second, due to the blurring of boundaries between work and personal life, the time-spatial job crafting is presented, i.e. the ability to choose a suitable place and time for work, to change the location of work, to change time or task if they do not match with each other, and to adjust work tasks to the current place and time of work, and his role in remote work. Thirdly, due to the increased autonomy to plan and perform one’s activities and the absence of factors that externally structure the work process and methods of performing tasks, the importance of self-leadership skills, which include the ability to act independently, plan one’s activities, set goals and achieve them, is highlighted. Finally, the article also presents the practical possibilities of psychological detachment from work, mastery of distance work and self-leadership development in the organization.
Keywords: remote work; psychological detachment; self-leadership; time-spatial job crafting